Effect Of Ni3ti Formation On The Oxidation Kinetics Of Niti Shape Memory Alloys - Nawawi, Nazihah (2014)
This research focusing on failure/damage response and energy absorption on different constituent material of thermoplastic honeycomb sandwich structure with three different core thicknesses of 10, 30 and 60 mm. In this present investigation, the interest will be on the fabrication of laminated composites skin, polypropylene (PP) and polycarbonate (PC) thermoplastic honeycomb core subjected to low velocity impact test of impacted energy 20, 60, 120 J. Curing method of the composite laminates of 5 layers E-glass fiber with orientation [0/90/±45/0/90] by using vacuum bagging is used with collaboration with the industry, AMREC Sirim Berhad, Kulim. Relevant properties of the composite skin was measured by conducting a series of properties test, such as, compression test, tensile test and three point bending test with rate sensitivity of 1 mm/min. This research of the composite sandwich structure also included identification on the localized damage and globalised damage on the structural / material integrity due to the drop weight impact through microstructure analysis. Quantification of the energy absorption capacity of the composite materials will be determined through different failure mode by computing energy-balance model for structural design optimization. In order to obtain the energy-balance model, other than low velocity impact test, three point flexural tests and indentation test will be carried out concurrently, energy dissipation by bending/shear and contact can also be determined. For the first time, the energy-balance model is extended to predict energy partitioning in order to understand how the energy of the impactor is absorbed by the dynamically loaded sandwich structure. Thus, improved structural materials can contribute to improved performance by introducing the failure mode map and failure recognition for advanced composite material according to the damage factor and energy level. In addition, compression after impact (CAI) is carried out to determine the strength reduction of the sandwich structure. As a conclusion from this study, energy absorbed and energy dissipated by the laminates and sandwich structure are obtained. Besides comparison between the toughness and stiffness of the materials, failure characterization is obtained as well